Systematic Review Of Risk Factor Of Intestinal Parasite Infection - Nur Afidah Novitasari; Mohammad Zainal Fatah (Media Gizi Kesmas, 2021)
Background: Intestinal parasites infection is a common problem in the world. Intestinal parasites infection causes morbidity, mortality, and complication. Objectives: The purpose of this research was to identify the intestinal parasite infection risk factors by using a systematic review of intestinal parasite infection-related existing publications. Methods: This study used a systematic review method. A systematic review of intestinal parasite risk factors was then performed following PRISMA guidelines. The data source of this study was derived from the literature obtained through the internet in the form of research results from publications in journals that were conducted in Hindawi, PubMed, emedicalj, tandfonline, knepublishing, portalnepas, ojs unud, plos, jurnal.umsb, and publications were assessed against inclusion and exclusion criteria. The population is the research paper about prevalence and risk factors for intestinal parasites infection from 2013-2019 and 35 studies were used. Inclusion criteria were researched that identifies risk factors intestinal parasites infection and uses primary data for the research. Exclusion criteria were review study and use secondary data for the study. Data are presented in tabular form. Univariate analysis to see the average, minimum and maximum values, and frequency and percentage distribution. Results: The results of the systematic study analysis are that the most risk factors for intestinal parasite infection are age, sex, residence, toilet, washing hand with soap before a meal, shoe-wearing habit, trimming nails, eating undercooked food, personal hygiene, and source of drinking water. Conclusions: Intestinal parasites can occur in children, adolescents, and adults who are affected by demographic factors, clean and healthy lifestyle behaviors and lifestyle. Cleanliness, health, and lifestyle are aspects that need to be improved to prevent intestinal parasites. Keywords:  intestinal parasites infection, lifestyle, risk factor, systematic review